The abdominal aortic aneurysm-related disease model based on machine learning predicts immunity and m1A/m5C/m6A/m7G epigenetic regulation - Tian, Yu; Fu, Shengjie; Zhang, Nan; Zhang, Hao; Li, Lei (Frontiers in Genetics, 2023)
Abdominal aortic aneurysms (AAA) are among the most lethal non-cancerous diseases. A comprehensive analysis of the AAA-related disease model has yet to be conducted. Weighted correlation network analysis (WGCNA) was performed for the AAA-related genes. Machine learning random forest and LASSO regression analysis was performed to develop the AAA-related score. Immune characteristics and epigenetic characteristics of the AAA-related score were explored. Taken together, our study developed a reliable AAA-related disease model for predicting immunity and m1A/m5C/m6A/m7G epigenetic regulation. The pathogenic roles of four model genes, UBE2K, TMEM230, VAMP7, and PUM2, in AAA, are needed to be further validated by in vitro and in vivo experiments.